The clinical impact of malnutrition on the postoperative outcomes of patients undergoing gastrectomy for gastric cancer: Propensity score matched analysis of 2011–2017 hospital database. (December 2021) - Lee, David Uihwan; Fan, Gregory Hongyuan; Hastie, David Jeffrey; Addonizio, Elyse Ann; Han, John; Prakasam, Vibhav Narayan; Karagozian, Raffi
Summary: Background & aims: Malnutrition is a prominent feature of gastric cancer patients who suffer from gastric outlet obstruction, impaired peristalsis, and cancer-mediated disruptions in metabolic hemostasis. In this study, we systematically evaluate the impact of malnutrition on the postoperative outcome of patients with gastric cancer undergoing gastrectomy. Methods: 2011–2017 National Inpatient Sample was used to isolate patients with gastric cancer who underwent gastrectomy, who were stratified using malnutrition. The malnutrition-present cohort was matched to the malnutrition-absent controls using 1:1 propensity score-matching analysis, and compared to the following endpoints: mortality, length of stay (LOS), hospitalization costs, and postoperative complications. Results: 5309 were identified to have undergone gastric resection procedure for gastric cancer, from which there were 1044 with malnutrition and 1044 matched controls. Malnourished patients had higher mortality (6.80 vs 3.83% p = 0.003, OR 1.83 95% CI 1.23–2.73), LOS (17.2 vs 11.4 d p < 0.001), costs ($197, 702 vs $124, 133 p < 0.001), and were more often discharged to rehabilitation facilities. Malnourished patients had higher rates of wound complications (3.64 vs 1.25% p < 0.001, OR 3.00 95% CI 1.59–5.66), infection (6.90 vs 3.26% p < 0.001, OR 2.20 95% CI 1.45–3.34), and respiratory failure (6.80 vs 3.64% p = 0.002, OR 1.93 95% CI 1.29–2.89). In multivariate analysis, malnourished patients had higher rates of mortality (p = 0.002, aOR 1.87 95% CI 1.25–2.80), length of stay (p < 0.001, aOR 1.52 95% CI 1.48–1.55), costs (p < 0.001, aOR 1.61 95% CI 1.61–1.61) despite controlling for non-matched hospital variables. Conclusion: In this propensity score matched analysis, malnutrition is associated with increased postoperative mortality, LOS, and hospitalization costs in patients with gastric cancer undergoing gastric resection surgery.